Defects of Midbrain/Hindbrain Development: Defects of Anteroposterior and Dorsoventral Patterning - Biasco, Arturo; Dierna, Federica; Zanghì, Antonio; Vecchio, Michele; Falsaperla, Raffaele; Praticò, Elena R.; Maniaci, Antonino; Ruggieri, Martino; Polizzi, Agata (Journal of Pediatric Neurology, 2024)
The knowledge regarding the midbrain and the hindbrain (MBHB) malformations has been progressively increased in recent years, thanks to the advent of neuroimaging and genetic technologies. Many classifications have been proposed in order to well describe all of these patterns. The most complete and detailed one is based on the genetic and embryologic features that allow an easier and effective knowledge of these disturbs. It categorizes them into four primary groups: (1) Malformations resulting from early anteroposterior and dorsoventral patterning defects or the misspecification of MBHB germinal zones.(2) Malformations linked to later generalized developmental disorders that notably impact the brain stem and cerebellum, with a pathogenesis that is at least partially comprehended.(3) Localized brain malformations significantly affecting the brain stem and cerebellum, with a pathogenesis that is partly or largely understood, encompassing local proliferation, migration, and axonal guidance.(4) Combined hypoplasia and atrophy observed in presumed prenatal-onset degenerative disorders. Regarding diagnosis, brain stem malformations are typically identified during prenatal assessments, particularly when they are linked with anomalies in the cerebellum and cerebrum. Magnetic resonance imaging is the primary neuroimaging method in the evaluation of these malformations. The clinical characteristics of individuals with malformations in the midbrain or hindbrain are generally nonspecific. Common findings at presentation are hypotonia, motor retardation, ataxia, variable degree of intellectual disability, and abnormal eye movement (e.g., nystagmus, abnormal saccades, oculomotor apraxia, strabismus, and abnormal smooth pursuit). The complexity and the number of these MBHB malformations are constantly increasing. We will provide an overview of MBHB disorders, focusing on embryology, genetic, clinical, and neuroradiology features that could be helpful for clinicians and neuroscientist to understand process of these conditions.
Keywords: midbrain malformations; genetics; anteroposterior; dorsoventral; patterning; neurons